Co-Creation As A Moderator Between Social Media Marketing Activities And Trust On Smes’ Customers Purchase Intention - Saad, Ebtiessam Ali Labib (2019)
The advent of social media has changed consumers’ role into a more active one, and this has necessitated the need to understand their behaviours on social media platforms better. These platforms have inadvertently culminated in co-creation and resulting in more complexity as customers, business partners, and suppliers simultaneously collaborate. Due to the critical significance of social media marketing activities to drive business success, this study aims to identify the extent to which social media marketing activities affect Small-to-Medium Enterprises’ (SMEs’) customer purchase intention in developing countries like Saudi Arabia where purchasing power is one of the highest. Therefore, this study assesses the impact of entertainment, interaction, trendiness and word of mouth as social media marketing activities on purchase intention with co-creation as the moderator and trust and commitment as the mediators in a research framework based on Commitment-Trust Theory. A total of 833 validated questionnaires was used in this study, which was collected using purposive quota sampling and assessed with PLS-SEM. Findings showed that social media marketing activities has positive and significant relationships with trust, commitment, and purchase intention. Entertainment, trendiness, and word of mouth were positively and significantly related to trust, while interaction was not. Co-creation strengthened the relationship between social media marketing activities and trust. It was also found that social media marketing activities impact on purchase intention indirectly with the mediation of trust via commitment.